Zinc ameliorates intestinal barrier dysfunctions in shigellosis by reinstating claudin-2 and -4 on the membranes - Sarkar, Paramita (Am J Physiol Gastrointest Liver Physiol, 2019)
Whether zinc (Zn(2+)) regulates barrier functions by modulating tight-junction (TJ) proteins when pathogens such as Shigella alter epithelial permeability is still unresolved. We investigated the potential benefits of Zn(2+) in restoring impaired barrier function in vivo in Shigella-infected mouse tissue and in vitro in T84 cell monolayers. Basolateral Shigella infection triggered a time-dependent decrease in transepithelial resistance followed by an increase in paracellular permeability of FITC-labeled dextran and altered ion selectivity. This led to ion and water loss into the intestinal lumen. Immunofluorescence studies revealed redistribution of claudin-2 and -4 to an intracellular location and accumulation of these proteins in the cytoplasm following infection. Zn(2+) ameliorated this perturbed barrier by redistribution of claudin-2 and -4 back to the plasma membrane and by modulating the phosphorylation state of TJ proteins t hough extracellular signal-regulated kinase (ERK)1/2 dependency. Zn(2+) prevents elevation of IL-6 and IL-8. Mice challenged with Shigella showed that oral Zn(2+)supplementation diminished diverse pathophysiological symptoms of shigellosis. Claudin-2 and -4 were susceptible to Shigella infection, resulting in altered barrier function and increased levels of IL-6 and IL-8. Zn(2+) supplementation ameliorated this barrier dysfunction, and the inflammatory response involving ERK-mediated change of phosphorylation status for claudin-2 and -4. Thus, Zn(2+) may have potential therapeutic value in inflammatory diarrhea and shigellosis. NEW & NOTEWORTHY Our study addresses whether Zn(2+) could be an alternative strategy to reduce Shigella-induced inflammatory response and epithelial barrier dysfunction. We have defined a mechanism in terms of intracellular signaling pathways and tight-junction protein expression by Zn(2+). Claudin-2 and -4 are susceptible to Shigella infection, whereas in the presence of Zn(2+) they are resistant to infection-related barrier dysfunction involving ERK-mediated change of phosphorylation status of claudins.